Synthesis and characterization of chiral ionic liquids based on quinine, l-proline and l-valine for enantiomeric recognition - Sintra, Tânia E. (2021)
The separation of enantiomers remains a major challenge for the pharmaceutical industry. In this work, eight chiral ionic liquids (CILs) directly derived from the ‘chiral pool’ were synthesized and characterized in order to develop enantioselective systems, for the chiral resolution. According to their chiral cations, three different groups of CILs were prepared, namely based on quinine, L-proline and L-valine, and their enantiomeric recognition ability evaluated. For that purpose the diastereomeric interactions between a racemic mixture of Mosher's acid sodium salt and each CIL were studied using 19 F NMR spectroscopy. The remarkable chemical shift dispersion induced by some CILs demonstrates their potential application in chiral resolution. Additionally the optical rotation, thermophysical properties and ecotoxicity against the marine bacteria Aliivibrio fischeri of these chiral ionic liquids were addressed.